2014
DOI: 10.1016/j.hbrcj.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the corrosion initiation time of slag concrete using the artificial neural network

Abstract: This paper focuses on the Artificial Neural Network (ANN) as an alternative approach to simulate the corrosion initiation time of slag concrete obtained from the error function solution to Fick's second law of diffusion. The adopted network architecture consists of four neurons in the input layer, which represents the values of concrete cover depth, apparent chloride diffusion coefficient, chloride threshold value and surface chloride concentration, and one neuron in the output layer, which represents the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Neural networks are used to find the solutions to constrained optimization problems and can be applied for storing, recalling classifying and mapping data or patterns [16]. Some ANN models related to measuring steel corrosion in concrete are found in [8], [17], [18], [19], [20] and [21].…”
Section: Ann Modelling For Corrosionmentioning
confidence: 99%
“…Neural networks are used to find the solutions to constrained optimization problems and can be applied for storing, recalling classifying and mapping data or patterns [16]. Some ANN models related to measuring steel corrosion in concrete are found in [8], [17], [18], [19], [20] and [21].…”
Section: Ann Modelling For Corrosionmentioning
confidence: 99%
“…e results have revealed that, in terms of the regression coefficient R 2 and MSE, ANN models have provided better results than MLR. Other studies have used ANNs for predicting some durability-related properties of concrete [28][29][30][31][32][33][34][35]. ey concluded that ANN models could be used effectively in predicting the concrete durability properties.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…These approaches use input parameters to model responses, and the output models are validated by experimentation. For construction applications, ML algorithms estimate concrete strength [ 43 , 44 , 45 , 46 , 47 ], bituminous mixture performance [ 48 ], and concrete durability [ 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%